Improving Students' Reading Abilities Through Comics Media for Elementary School Students - Widiyanti, Alfiana Lulu; Tasya, Nikmatul; Muna, Fauzul; Zalzidan, Qeila Zahri; Ardianti, Sekar Dwi (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study aims to determine how much comic learning media improves students' reading ability in grade II at SD 2 Demaan Kudus. We conducted the study because the students appeared passive and demonstrated low learning processes and reading abilities. As a result, researchers used comics as a learning tool to improve learning. Research Methods: This study employs a classroom action research methodology. Students registered in grade II at SD 2 Demaan, totalling 25 people, are the subjects of this study. This research method uses classroom action research, consisting of two cycles with observation, reflection, and implementation of actions. Researchers work together with direct observers during the action and evaluate students' abilities. Finding/Results: Data analysis shows an increase in students' reading ability, especially in the pre-cycle (29%), cycle I (54%), and cycle II (72%). The results of reading ability activities also increased, as shown by 52% of students who were active in cycle I and 72% in cycle II. The results of the study indicate that students in grade II of SD 2 Demaan can improve their reading ability by using comic learning media.